2008
DOI: 10.3409/fb56_1-2.103-110
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of a Lipase from Gypsy Moth (Lymantria dispar L.) Larval Midgut

Abstract: Lipase activity of the gypsy moth (Lymantria dispar L.) was studied by the spectrophotometric method using crude homogenate of fifth-instar larval midgut tissues as the enzyme source and p-nitrophenyl caprylate (pNPC) as substrate. A Km value of 0.310mM and a Vmax value of 1.479U/mg prot. were obtained for this substrate. Among various p-nitrophenyl esters tested, maximum activity was obtained for p-nitrophenyl caprylate and p-nitrophenyl caprate. The enzyme was most active at alkaline pH, with maximum at pH 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 62 publications
3
8
0
4
Order By: Relevance
“…High temperature may interfere with hydrogen bond of enzyme causing denaturation of this enzyme [32]. Similar results have been shown in other insect lipases, as in gypsy moth Lymantria dispar [40], Rhynchophorus palmarum [41] and N . aenescens [16].…”
Section: Discussionsupporting
confidence: 61%
“…High temperature may interfere with hydrogen bond of enzyme causing denaturation of this enzyme [32]. Similar results have been shown in other insect lipases, as in gypsy moth Lymantria dispar [40], Rhynchophorus palmarum [41] and N . aenescens [16].…”
Section: Discussionsupporting
confidence: 61%
“…After 2 h of incubation, 60% of activity of PVL was lost at pH 10. Lipase of scorpion S. maurus lost only 35% of its activity after 4 h incubation at pH 11 and pH under 5 (Zouari et al 2005), as well as lipase from the Asian gypsy moth Lymantria dispar (Mrdakovic et al 2008) and squid O. bartramii (Sukarno et al 1996). Lipase activity decreased in Rodnius prolixus and Cephaloleia presignis at pH>8.0 (Arreguín-Espinosa et al 2000; Grillo et al 2007); these evidences showed that the pH stability of lipases differs between species.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme activities were measured in triplicate and controls without enzyme or without substrate were included. Lipase activity was determined using p-nitrophenyl caprylate as the substrate, by continuous monitoring of the release of p-nitrophenol at 410 nm (Mrdaković et al, 2008). Specific enzyme activities were expressed as U/mg of midgut protein, and one unit of enzyme activity is defined as the amount of enzyme that liberates 1 µmol of reaction product per minute, under the given assay conditions.…”
Section: Enzyme Assaysmentioning
confidence: 99%